Low Complexity Selective Adaptive Multicarrier DS-CDMA Receiver - Ahmed El-Sayed El-Mahdy; Maged Ahmed (Universitas Ahmad Dahlan, 2013)
In this paper, selective adaptive (SA) receiver for Multicarrier Direct Sequence Code Division Multiple Access (MC DS-CDMA) system is presented. This receiver has high performance and at the same time reduces the multiple access interference (MAI) of the MC DS-CDMA) system with low computational complexity. The performance of SA receiver is measured in terms of the bit error rate (BER). An upper bound expression of the BER for the SA receiver under Rayleigh fading channel condition is derived and validated by computer simulations. Moreover, the implementation complexities of the SA receiver is compared with the Adaptive Parallel Interference Cancellation (APIC) receiver.